O processo de recoconstrução da linguagem na interação entre os sujeitos afásicos - Barros, Paula Fernanda Silva de (2011)
Studies of aphasia have had a long journey and walked from the organismic perspective, arriving at the present time with the prospect linguistic and discursive roots where they come from solidifying. This paper briefly outlines the history of aphasia and this way of perspective, focusing on the linguistic-discursive perspective. The need for research directed by this investigative focus has intensified concerns and reflections in relation to interaction help in this reconstruction process, which outlined the objectives relevant theme. This study aims to discuss how it feels the process of reconstruction of the language through interaction between participants in Group aphasic aphasic coexistence of the Catholic University of Pernambuco (UNICAP). This discussion involved the identification of strategies that facilitate the production of discourse and the definition of interference from partners and non-aphasic aphasics in the reconstruction of language among the subjects from the locus investigated. The characterization involved an investigative methodological orientation toward knowledge of the Analysis of Speech French Line, the parameter under which it gave to analyze the speech of aphasic patients, taken from transcripts made for each meeting. From the research findings have shown us that the interaction is done in many moments of Living Group and is more common than among aphasic aphasic and non-aphasics. Given this, we conclude that there is interaction as the reconstruction of language and between aphasic and nonaphasic, mediating strategies are needed for this reconstruction is consolidated. With this we conclude that the interaction is present, functioning as a mediator in the reconstruction of the language of aphasic Group Coexistence of aphasic and aphasic's not UNICAP.